Comportamiento agronómico de cuatro hortalizas de fruto con tres abonos orgánicos en el centro experimental “La Playita”, de la Universidad Técnica de Cotopaxi - La Maná. Quevedo. - Arriaga Muñoz, Lenny Noraida (2013)
This research was conducted at the Experimental Center "La Playita", of the Technical University of Cotopaxi. The main objective was to determine the agronomic performance of four vegetables of fruit with three organic fertilizers in the Centre Experimental "La Playita", of the Technical University of Quito - La manna. A complete block design to the random (DBCA) composed of five treatments and three replicates was used, the treatments were: tomato, pepper, cucumber, and eggplant; fertilizers earthworm Humus, water hyacinth and combination of Jacinto de Agua + Vermicompost. The results were: height of the tomato to 60 days for the Jacinto de Agua with 119.40 cm. number of fruit per harvest treatment witness with the greatest average fourth harvest with 2.80 fruits. Diameter of Vermicompost and Jacinto de Agua tomato reached higher averages in the fourth harvest with 7.27 cm. For the weight of fruit in the fourth harvest treatment witness with 271.72 g. Height of peppers 60 days to harvest, fruit diameter and weight of fruit in the fourth vintage control with 64.58 treatment; 8.56 and 83.94 cm; in the fourth harvest Vermicompost treatment obtained higher averages in fruit length and number of fruits with 5.32 cm and 2.33 fruits. For the total yield per hectare treatment water hyacinth achieved the highest average with 0.59 t ha-1…………………………………..